Bond Strength between Glass Fiber Fabrics and Low Water-to-Binder Ratio Mortar: Experimental Characterization - Daniel Bohling; Andrzej Cwirzen; Karin Habermehl-Cwirzen (Advances in Civil Engineering)
Full utilization of mechanical properties of glass fiber fabric-reinforced cement composites is very limited due to a low bond strength between fibers and the binder matrix. An experimental setup was developed and evaluated to correlate the mortar penetration depth with several key parameters. The studied parameters included fresh mortar properties, compressive and flexural strengths of mortar, the fabric/mortar bond strength, fabric pullout strength, and a single-lap shear strength. Results showed that an average penetration of mortar did not exceed 100 µm even at a higher water-to-binder ratio. The maximum particle size of the used fillers should be below an average spacing of single glass fibers, which in this case was less than 20 µm to avoid the sieving effect, preventing effective penetration. The pullout strength was strongly affected by the penetration depth, while the single-lap shear strength was also additionally affected by the mechanical properties of the mortar.